2009
DOI: 10.1103/physreve.79.056402
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical and spherical ion-acoustic envelope solitons in multicomponent plasmas with positrons

Abstract: The nonlinear wave modulation of planar and nonplanar (cylindrical and spherical) ion-acoustic envelope solitons in a collisionless unmagnetized electron-positron-ion plasma with two-electron temperature distributions has been studied. The reductive perturbative technique is used to obtain a modified nonlinear Schrödinger equation, which includes a damping term that accounts for the geometrical effect. The critical wave number threshold Kc, which indicates where the modulational instability sets in, has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Linear aspects of the system have been considered in several studies (Iwamoto, 1993;Stewart and Laing, 1992;Zank and Greaves, 1995). Nonlinear processes have been a particularly rich area including such aspects as solitary waves (Dubinov et al, 2006;El-Shamy et al, 2010;Ghosh et al, 2012;Gordienko and Dubinov, 2008;Roy et al, 2012;Sabry, 2009), solitons (Cattaert and Kourakis, 2005;Sabry et al, 2009;Zank and Greaves, 1995), double layers (Alterkop et al, 2007;Mishra et al, 2007), collisionless reconnection processes (Bessho and Bhattacharjee, 2005;Hosseinpour and Vekstein, 2008) electrostatic and electromagnetic wave phenomena (El-Taibany and Mamun, 2012;Ghosh et al, 2012;Gordienko and Dubinov, 2007;Kourakis et al, 2007;Mushtaq and Khan, 2008), and vortices (Shukla et al, 2003).…”
Section: Classical Electron-positron (Pair) Plasmasmentioning
confidence: 99%
“…Linear aspects of the system have been considered in several studies (Iwamoto, 1993;Stewart and Laing, 1992;Zank and Greaves, 1995). Nonlinear processes have been a particularly rich area including such aspects as solitary waves (Dubinov et al, 2006;El-Shamy et al, 2010;Ghosh et al, 2012;Gordienko and Dubinov, 2008;Roy et al, 2012;Sabry, 2009), solitons (Cattaert and Kourakis, 2005;Sabry et al, 2009;Zank and Greaves, 1995), double layers (Alterkop et al, 2007;Mishra et al, 2007), collisionless reconnection processes (Bessho and Bhattacharjee, 2005;Hosseinpour and Vekstein, 2008) electrostatic and electromagnetic wave phenomena (El-Taibany and Mamun, 2012;Ghosh et al, 2012;Gordienko and Dubinov, 2007;Kourakis et al, 2007;Mushtaq and Khan, 2008), and vortices (Shukla et al, 2003).…”
Section: Classical Electron-positron (Pair) Plasmasmentioning
confidence: 99%
“…(24), we can get the following nonlinear dispersion relation [31,49] for the amplitude modulation of the IAWs modes:…”
Section: Nonlinear Dispersion Relationmentioning
confidence: 99%
“…Since the effects of parameters β, δ and γ on critical wave number threshold k c have been discussed in a electron-positron-ion plasma in Ref. [31], we just investigate the effects of the nonextensive index q, dust concentration α, wave number k and cold electron to positive ion density ratio µ on the MI and rogue waves in this paper.…”
Section: Nonlinear Dispersion Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies indicate that the properties of solitary waves in bounded nonplanar geometry are very different from those in unbounded planar geometry (Maxon and Viecelli 1974;Maxon 1978). Very recently, Sabry et al (2009) investigated the nonlinear wave modulation of planar and nonplanar cylindrical and spherical ion-acoustic envelope solitons in a collisionless, unmagnetized electron-positron-ion plasma with two-electron temperature distributions by employing the reductive perturbation method. The authors reported a modulation instability period for the cylindrical and spherical wave modulation which was non-existent in the planar geometry.…”
Section: Introductionmentioning
confidence: 98%